2018
DOI: 10.1186/s40337-018-0210-6
|View full text |Cite
|
Sign up to set email alerts
|

Emotional eating and weight regulation: a qualitative study of compensatory behaviors and concerns

Abstract: BackgroundEmotional eating, or overeating in response to negative emotions, is a behavior endorsed by both normal weight and people with overweight/obesity. For some individuals, emotional eating contributes to weight gain and difficulties losing weight. However, there are also many who engage in emotional eating who maintain a normal weight. Little is known about the mechanisms by which these individuals are able to regulate their weight.MethodsThe present study seeks to gain insight into the behaviors of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 45 publications
1
48
0
6
Order By: Relevance
“…There are several explanations for the insignificant relationship between snacking and BMI: (1) snacking not only may involve the consumption of unhealthy products (e.g., sweets, chips) but also can be healthy (e.g., nuts, fruits, vegetables), and these snacks do not often lead to weight gain [35,36], (2) to prevent weight gain due to snacking, people may also use dietary restriction (e.g., eat less for breakfast or supper) or use other compensatory behaviours (e.g., physical exercise, laxatives) [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several explanations for the insignificant relationship between snacking and BMI: (1) snacking not only may involve the consumption of unhealthy products (e.g., sweets, chips) but also can be healthy (e.g., nuts, fruits, vegetables), and these snacks do not often lead to weight gain [35,36], (2) to prevent weight gain due to snacking, people may also use dietary restriction (e.g., eat less for breakfast or supper) or use other compensatory behaviours (e.g., physical exercise, laxatives) [2].…”
Section: Discussionmentioning
confidence: 99%
“…Maladaptive food-related behaviours (e.g., emotional eating, overeating, snacking, restrictive eating) are identified among people with normal weight and with excessive body weight (overweight/obesity) [1][2][3]. Interestingly, a lot of current research refers to the relationship between emotional state and eating behaviours [e.g., [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence is known to be a stressful developmental period, and emerging research supports the need to address psychosocial stress as a factor in obesity prevention and management [71][72][73][74]. The psychosocial stress arising from poor body image and social ostracization, especially associated with adolescent obesity, may further promote stress and corresponding health-compromising coping mechanisms [75].…”
Section: Physiological Stressmentioning
confidence: 99%
“…However, evidence of ME training on weight is mixed and additional research to determine comparative and long-term effects is needed 49. In recent years, EE—that is overeating in response to negative emotions50—has been seen as a potential explanatory factor of the complexity of overweight and obesity 51. It has been observed that: (1) EE interacts with loss of control eating, increasing disordered eating attitudes, BMI and adiposity52; (2) EE is implicated in the use of compensatory behaviours to regulate weight50; and that (3) decreases in EE are associated with weight loss success in overweight adults 53.…”
Section: Introductionmentioning
confidence: 99%